ORIENTASI PENDAMPINGAN PERLINDUNGAN HARTA ANAK YATIM OLEH WALI DALAM QS AN NISA AYAT 2 DI MAJLIS TA’LIM AN-NUR BABELAN, BEKASI - Kholilurrohman Kholilurrohman; Nurkhafifah Tamsyur; Mohamad Zainal Arifin; Salman Faris; Ahmad Husnul Hakim; Wardatul Jannah (MADANI Abdimas : Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
Islamic law instructs the guardians of orphans not to arbitrarily affect the orphans and their property. Because children are part of the younger generation as one of the human resources who have a strategic role in forming a better family. Guardians should not behave unjustly towards orphans. he law recommends the guardian to make a list of assets so that the guardian's property is not mixed with the orphan's property and in Law No. 1 of 1974 concerning Marriage, it is regulated about the prohibition of using and consuming excessively, moving and selling the 1 Nurkhafifah Tamsyur property of orphans. However, the reality of society, in the care of orphans has not been carried out as specified in Islamic teachings. In maintaining the property of an orphan by a guardian, the guardian must have a concept in managing finances on a monthly or yearly basis, it is better if he develops his property so that it is "alive" and not "frozen" in order to get benefits to cover his daily life. And if the child has reached puberty, is an adult or can manage his own property, his property must be handed over honestly according to the assets he has and when submitting he must present witnesses so that there is a guarantee for his responsibility so as not to cause disputes or quarrels that can lead to disputes and conflicts. prejudice, By understanding the maintenance of the orphan's property, the guardian or the one who is entrusted with the care of the orphan's property can be more careful and pay attention to the property as best as possible starting from the time it is guarded until the time it is handed over when the child is an adult. In QS. An - Nisa verse 2 explains about the care of orphans by guardians when the orphans are mature (adults) they can manage their own assets